STRATEGI OPTIMALISASI BAHAN BAKU LATEKS PADA INDUSTRI KARET JENIS RIBBED SMOKED SHEET (RSS) - Vevi Oktavia; Erdi Suroso; Tanto Pratondo Utomo (Jurnal Teknologi & Industri Hasil Pertanian, 2014)
One of the problems in the ribbed smoked sheet (RSS) production  is low quality of field latex, used as a raw material.  The objective of this research was to identify issues that affect the  latex qualities and  to analize optimization strategy for  improving its quality for RSS raw material.  The study was conducted by using survey method to collect primary and secondary data, then the data were  analyzed descriptively.  The results showed that the weighting values for the strength factor was 2,431 and 2,394  for weakness factor, the difference obtained was 0,037.  Meanwhile,  the opportunity factor was 2,794 and the threat factor was2,134,  the difference was obtained by 0,659.  Predominant issues affected field latex quality were rubber tree clones,  plant treatment, the pracoagulation of latex and the latex bubble at the time of testing.  Optimization strategies that can be applied include: planting the recommended and certified rubber clones , which bring  benefit both in terms of wood and rubber qualities, to maintain  the country performance  as the second largest production area by intensifying  the maintenance,  and scheduling the fertilizing time of the plants, encouraging  people to replant with high resistant and recommended clones, and to improve the field latex qualities as determined in  SNI 06-2047-2002 in order to compete along with increasing demand for rubber. Keywords : optimization strategy of latex, ribbed smoked sheet